(untitled) (Global Journal of Science Frontier Research, 2023)
Study was realized on July 2021 inside of the Institute of Agricultural Research for Development IRAD Main objective of study is to determine the dose of mineral fertilizers and densities which responses well to the rice culture especially of the variety Nerica L36 in a humid area of the valley of Benou Treatments are constituted of fourth levels of doses and repeated 3 times